Warung Madura’s Survival Strategy Amidst the Challenges of the Digital Economy - Sukidin, Sukidin; Abshor, Faqih Ulil; Ani, Hety Mustika; Kusumawati, Astrian; Widiastuti, Anik (Jurnal Economia, 2025)
Warung Madura characterized by a simple business model and strong work ethic, have become an integral part of Indonesia’s microeconomy. The rapid development of technology and digitalization, however, presents challenges for shop owners to remain relevant and competitive in an increasingly digital market. This study aims to examine the work ethic and survival strategies of Warung Madura in the context of digital transformation. A qualitative approach was employed through in-depth interviews and participant observation with four shop owners in Jember who have operated their businesses for at least one year. The findings reveal that perseverance, discipline, and quality service constitute essential capital for sustaining business operations. Although limited technological access and digital literacy remain constraints, some owners have begun utilizing social media and simple digital platforms such as WhatsApp. The study concludes that work ethic, adaptability, creativity, and digital literacy are key to ensuring the sustainability of Warung Madura